Comparative Immunovirological and Clinical Responses to Antiretroviral Therapy Between HIV-1 Group O and HIV-1 Group M Infected Patients. (7th May 2019) - Kouanfack, Charles; Unal, Guillemette; Schaeffer, Laura; Kfutwah, Anfumbom; Aghokeng, Avelin; Mougnutou, Rose; Tchemgui-Noumsi, Nathalie; Alessandri-Gradt, Elodie; Delaporte, Eric; Simon, François; Vray, Muriel; Plantier, Jean-Christophe; et al.
Abstract: Background: Little is known about impact of genetic divergence of human immunodeficiency virus type 1 group O (HIV-1/O) relative to HIV-1 group M (HIV-1/M) on therapeutic outcomes. We aimed to determine if responses to standardized combination antiretroviral therapy (cART) were similar between groups despite strain divergence. Methods: We performed an open nonrandomized study comparing the immunological, virological, and clinical responses to cART based on 2 nucleoside reverse transcriptase inhibitors plus 1 ritonavir-boosted protease inhibitor, in naive and paired HIV-1/O vs HIV-1/M infected (+) patients (ratio 1:2), matched on several criteria. The primary endpoint was the proportion of patients with undetectable plasma viral load (pVL, threshold 60 copies/mL) at week (W) 48. Secondary endpoints were the proportion of patients with undetectable pVL at W24 and W96 and CD4 evolution between baseline and W24, W48, and W96. Results: Forty-seven HIV-1/O + and 94 HIV-1/M + patients were included. Mean pVL at baseline was significantly lower by 1 log for HIV-1/O + vs HIV-1/M + patients. At W48, no significant difference was observed between populations with undetectable pVL and differences at W24 and W96 were not significant. A difference in CD4 gain was observed in favor of HIV-1/M at W48 and W96, but this was not significant when adjusted on both matched criteria and pVL at baseline. Conclusions: Our data demonstrate similar immunovirological and clinical response between HIV-1/O + and HIV-1/M + patients. They also reveal significantly lower baseline replication for HIV-1/O variants, suggesting specific virological properties and physiopathology that now need to be addressed. Clinical Trials Registration: NCT00658346. Abstract : Our study shows similar immunovirological and clinical responses between human immunodeficiency virus type 1 group O (HIV-1/O) and HIV-1 group M (HIV-1/M) infections despite genetic divergence between group M and O viruses, but reveals a significantly lower replication by 1 log of these variants compared to HIV-1/M.